THE ROLE OF THE NOTARY IN SALE AND PURCHASE AGREEMENT FOR MOVABLE PROPERTY (BASED ON DECISION NUMBER 33/PDT.G/2018/PN.BLK) - Melnia, Nur Fitri; Susilowati Suparto (DE'RECHTSSTAAT, 2024)
Article 15 paragraph (2) letter e of Notary Regulation states that a Notary has the authority to provide legal advice regarding the formation of a legal document. Sale and purchase agreement with an installment system is an anonymous agreement. The object of journal writing is Decision Number 33/Pdt.G/2018/PN.Blk. This research is descriptive analytical using a normative juridical approach, then the data is analyzed using qualitative juridical data analysis. Based on the research, the first result obtained is the authority of a Notary in legal counseling is only regulated in Article 15 paragraph (2) letter e of Notary Regulation and the installment sale and purchase agreement document is an unnamed agreement because there is no specific regulation in the law and the Civil Code in Indonesia, but this agreement still provides legal certainty. The second result is Decision Number 33/Pdt.G/2018/PN.Blk. The defendant has defaulted and obliged to pay the remaining payment. The Plaintiff must hand over to the Defendant 3 (three) documents of ownership of the vehicle being traded after the Defendant's debt is paid off.